Menjaga Kelangsungan Bisnis dengan Aplikasi Knowledge Management System pada CV. Kahati Ciptaning Bhumi - Beji, Depok - Ardijan Handijono; Rudy Irawan Gunarto; Reno Virlandana A. (Abdimisi, 2021)
Currently, kitchen sets are very popular. One of the business actors in making kitchen sets is Mr. Ahadi Cahya Pratama who in 2020 started a service business for making interior, kitchen sets and custom furniture with a CV. Kahati Ciptaning Bhumi, Depok. The main problem faced is how to save the expertise and experience of the experts because they are worried that the experts may move to other companies, or die. The approach method used in PKM activities is brainstorming, presentation and discussion. There are several solutions that we offer, namely regarding the importance of forming a business entity, how to use social media for promotion, how to manage business finances, and how organizations store expertise and experience to maintain business. The expectations generated from this PKM are: 1) increased sales with marketing technology-based, 2) Expertise’s expertise and experience can be stored safely, and 3) better financial bookkeeping.